Catalytically competent non-transforming H-RASG12P mutant provides insight into molecular switch function and GAP-independent GTPase activity of RAS - Metehan, İlter; Şensoy, Özge (Nature Publishing Group, 2019)
RAS mutants have been extensively studied as they are associated with development of cancer; however, H-RASG12P mutant has remained untouched since it does not lead to transformation in the cell. To the best of our knowledge, this is the first study where structural/dynamical properties of H-RASG12P have been investigated -in comparison to H-RASWT, H-RASG12D, RAF-RBD-bound and GAP-bound H-RASWT- using molecular dynamics simulations (total of 9 ?s). We observed remarkable differences in dynamics of Y32. Specifically, it is located far from the nucleotide binding pocket in the catalytically-active GAP-bound H-RASWT, whereas it makes close interaction with the nucleotide in signaling-active systems (H-RASG12D, KRAS4BG12D, RAF-RBD-bound H-RASWT) and H-RASWT. The accessibility of Y32 in wild type protein is achieved upon GAP binding. Interestingly; however, it is intrinsically accessible in H-RASG12P. Considering the fact that incomplete opening of Y32 is associated with cancer, we propose that Y32 can be targeted by means of small therapeutics that can displace it from the nucleotide binding site, thus introducing intrinsic GTPase activity to RAS mutants, which cannot bind to GAP. Therefore, mimicking properties of H-RASG12P in RAS-centered drug discovery studies has the potential of improving success rates since it acts as a molecular switch per se.
Keywords: RAS; Catalytically Competent Nontransforming; Molecular Switch Function